Canadian Science Policy and the Retreat from Transformative Politics: The Final Years of the Science Council of Canada, 1985-1992 - Clowater, G. (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2012)
The Science Council of Canada (1966-1992) operated as an ‘arms-length’ agency providing science policy advice and recommendations to the federal government. The Council was always a voice for state interventionism. In the late 1970s, it turned to the politically sensitive issue of industrial policy and advocated a nationalistic, ‘transformative politics’ through its defense of technological sovereignty. An examination of its research and policy recommendations, and the controversies they excited, reveals that the Council’s struggle against new policy trends in its final years paralleled larger transitions in public perceptions of the role of government in Canadian society. Its 1992 dissolution symbolized Canada’s reorientation from a state-directed to a market-oriented approach to science and technology policy-making. This paper reviews the Council’s guiding philosophy and discusses its history within two larger contexts: the Canadian political debate over continentalism, and evolving conceptions of science, technology, and innovation, and the prospects for their management.